Evaluation of Good Distribution Practice (GDP) Implementation at the Provincial Pharmacy and Health Logistics Installation (IFLK) of Riau - Nofriyanti; Devi Safitri; Nurzakyya Tinnisa; Ramona, Paula (Indonesian Journal Publisher, 2025)
This study aimed to evaluate the implementation of Good Distribution Practice (GDP) at the Provincial Pharmacy and Health Logistics Installation (IFLK) of Riau. The research employed direct observation, document review, and active participation in pharmaceutical management activities, including planning, procurement, storage, distribution, recording, and monitoring. The evaluation focused on three key areas: general drug management, cold chain products, and controlled substances such as narcotics and psychotropics. The results showed that all assessed aspects of GDP were properly implemented at IFLK Riau, including the application of FIFO and FEFO principles, well-maintained cold chain facilities, secure storage for controlled drugs, and systematic stock documentation. Overall, the implementation of GDP at IFLK Riau was considered optimal and compliant with national standards, ensuring the quality, safety, and availability of medicines within the region. These findings emphasize the critical role of pharmacists in maintaining the integrity and sustainability of the pharmaceutical distribution system.